Spatial and temporal variability in geomorphic change at tidally influenced shipwreck sites: The use of time‐lapse multibeam data for the assessment of site formation processes. Issue 3 (9th January 2021) - Majcher, Jan; Quinn, Rory; Plets, Ruth; Coughlan, Mark; McGonigle, Christopher; Sacchetti, Fabio; Westley, Kieran
Abstract: Shipwrecks are an integral part of our maritime archaeological landscape and are associated with diverse societal and cultural interests, yielding significant management challenges. Coupled hydrodynamic and geomorphological processes significantly impact the effective in situ preservation of these fragile sites. In this study, we assess sediment budget change and hydrodynamic triggers at metal‐hulled shipwrecks lost between 1875 and 1918, all located in the tidally dominated Irish Sea at depths between 26 and 84 m. This is conducted using time‐lapse, multibeam echosounder surveys at multiannual, annual, and weekly time steps, supported by sediment grain‐size analysis, modeled ocean currents, and shallow seismic data. Results indicate significant changes at all time steps for sites located in sand‐dominated environments, whereas the seabed around shipwrecks settled in multimodal sediments shows virtually no change outside of measurement errors (±30 cm). Variability in geomorphic change is attributed to local environmental factors, including bed shear stress, sediment supply, and spatial barriers to scour. We demonstrate that individual wrecks in similar shelf sea regions can be in very different equilibrium states, which has critical implications for the in situ management of underwater cultural heritage. Abstract : Conceptual site dynamics models for the investigated sand‐dominated (a) and multimodal sites (b) with a corresponding site preservation estimation for the two categories (c). Rapid changes in the site dynamics due to continuous sediment supply and/or single events cause accelerated degradation and lower site preservation. In contrast, stable periods favour preservation which is, however, always decreasing due to chemical and biological deterioration.